Disrupting the Narrative on Recruiting Graduate Students of Color in Counselor Education - Carlos P. Hipolito-Delgado; Diane Estrada; Marina Garcia (Teaching and Supervision in Counseling, 2021)
The voices of students of color are largely absent in the literature on graduate student recruitment in counselor education. The existing literature focuses on university personnel and can portray a deficit perspective of students of color. Using grounded theory and a critical race theory framework, we sought to develop a theory that described the motivations of graduate students of color for pursuing counselor education. We interviewed 19 graduate students of color and used a constant comparative method to understand their motivations for and supports utilized in pursuing counselor training. Grounded in our participants’ counternarratives, we identified a theory to describe their drive to serve marginalized communities, to attend programs committed to diversity, and the supports they received in applying to graduate school. Based on this theory we provide implications for how counselor education programs can demonstrate a commitment to diversity and support graduate students of color through the application process.
Keywords: recruitment; graduate students of color; counselor education